2010
DOI: 10.1016/j.pepi.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state (EOS) and collapse of magnetism in iron-rich meteorites at high pressure by first-principles calculations

Abstract: We have calculated electronic and structure properties, equation of state (EOS) and collapse of magnetism of different meteoritic materials at high pressure using density functional theory (DFT). The fully optimization structures are obtained by minimization of the total energy and atomic forces of iron rich materials, which are in good agreement with the experiment. Phase transition of Fe 2 P (C22 type structure) barringerite into Fe 2 P (C23 type structure) allabogdanite is calculated to be 26 GPa. Collapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
2
2
1
Order By: Relevance
“…Since experimental or theoretical data are not available for magnetic moments of C23 structure considered in the present work, we cannot make a comparison. However, the average magnetic moment per Fe atom ( 0.84 µ B ) is in reasonable agreement with the earlier DFT result (0.7 µ B ) [26].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Since experimental or theoretical data are not available for magnetic moments of C23 structure considered in the present work, we cannot make a comparison. However, the average magnetic moment per Fe atom ( 0.84 µ B ) is in reasonable agreement with the earlier DFT result (0.7 µ B ) [26].…”
Section: Resultssupporting
confidence: 91%
“…As evident from the figure 1, no phase transformation occurs between C22 and C23 phase under compression up to 80 GPa. This is in disagreement with the computational results presented in the earlier study [25], where they predict C22 to C23 phase transformation under a pressure of 26 GPa. However, our results are in accordance with the experimental observations [12,13], where C22 to C23 structural transformation under pressure is observed only when the samples are heated to higher temperatures of ∼1400 K.…”
Section: Electronic Structurecontrasting
confidence: 99%
See 1 more Smart Citation
“…The variations in the predicted lattice parameters 44,86,88,[90][91][92][93]95,96) and elastic constants (Tables 6 and 7) using first-principles calculations were studied. It was found that the variations of the predicted lattice parameters among researchers is less than 1% and the variations of the elastic constants among the researchers is several %.…”
Section: Variations Among Researchers In the Results Of First-princip...mentioning
confidence: 99%
“…( 1), which expresses the relationship between P obtained from ∂E tot /∂V and V. This method of obtaining B 0 F has been attempted by many researchers as a method to obtain the bulk modulus of cementite using first-principles calculations. Table 6 44,[86][87][88][89][90][91][92][93][94] summarizes the reported values of B 0 F , B' 0 F , and V 0 , the EOS, and the range of pressure and volume values. Since cementite is FM at room temperature and becomes NM under high pressure, the values in Table 6 are shown separately according to the magnetic state, that is, either in the FM state or in the NM state.…”
Section: Bulk Modulus B F Of Cementite Estimated Using the Equation O...mentioning
confidence: 99%